A novel approach to ameliorate experimental milk allergy based on the oral administration of a short soy cross-reactive peptide. (1st June 2021) - Candreva, Ángela María; Smaldini, Paola L.; Cauerhff, Ana; Petruccelli, Silvana; Docena, Guillermo H.
Highlights: A soy peptide presents cross-reactive immunodominant T epitopes with bovine caseins. A soy peptide presents cross-reactive immunodominant B epitopes with bovine caseins. Peptide capacity to crosslink IgE is low and prevents IgE-mediated experimental milk allergy. Oral administration of a soy peptide prevents IgE-mediated experimental milk allergy. Abstract: Food allergy is on the rise, and preventive/therapeutic procedures are needed. We explored a preventive protocol for milk allergy with the oral administration of a Gly - m-Bd-30K soy-derived peptide that contains cross-reactive epitopes with bovine caseins. B/T-cross-reactive epitopes were mapped using milk-specific human sera and monoclonal antibodies on overlapping and recombinant peptides of Gly - m-Bd-30K by SPOT and cell proliferation assays. Bioinformatics tools were used to characterize epitopes on the 3D-modelled molecule, and to predict the binding to HLA alleles. The peptide was orally administrated to mice that were then IgE-sensitized to milk proteins. Immunodominant B-epitopes were mainly located on the surface of the Nt-fragment. The use of a soy-peptide-containing an immunodominant cross-reactive T -epitope, along with a single B epitope, prevents IgE-mediated milk sensitization through the induction of Th1-mediated immunity and induction of blocking IgG. The use of a safe soy-peptide may represent a promising alternative for preventing milk allergy.